A new multiparty identification scheme based on nearring root extraction problem. (2nd January 2019) - Arunma, M.; Ezhilmaran, D.
Abstract: In this paper, we propose a Multiparty Identification Scheme based on Nearring root Extraction Problem. This scheme enables more than two or three parties to prove their identity among themselves. We have chosen Nearring root extraction problem as a basis for our scheme. An adversary finds difficult to break the scheme as he/she finds very hard to extract the nth root for a given near polynomial ring.